Application of service quality dimensions in fulfilling tourist satisfaction at Kaki Langit Tourism Village - Risma Wulansari; Salma Renatha Madani; Tita Kusuma Ayu (Journal of Rural Tourism, 2024)
Purpose - The purpose of this study is to analyze the quality of service at Kaki Langit Tourism Village in Yogyakarta. The study explores how service quality influences tourist satisfaction, destination image, and overall tourist experience.Methodology/Design/Approach - The research uses a qualitative approach, with data collection techniques including interviews and observations to gather both written and oral data on service quality. The study focuses on five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. Finding - The study finds that the service quality dimensions at Kaki Langit Tourism Village have been implemented but are still in the development stage. While efforts have been made to improve service quality, further follow-up and development are required to optimize the application of service quality and ensure the best possible experience for tourists.Originality/Value - This research highlights the importance of continuous development and improvement in service quality to enhance tourist satisfaction in tourism villages. It provides valuable insights for further refining service quality practices at Kaki Langit Tourism Village to achieve optimal results.